Organic and carbon gels : from laboratory synthesis to applications /: from laboratory synthesis to applications. (2019) - Arenillas, Ana; Menéndez, J. Angel; Reichenauer, Gudrun; Celzard, Alain; Fierro, Vanessa; Maldonado Hodar, Francisco José; Bailón-Garcia, Esther; Job, Nathalie
No abstract available